The hidden curriculum and its relevance in vocational education (Research, Society and Development, 2020)
This article presents a discussion about the Hidden Curriculum whose objective was to understand the contribution of this theme to the teaching in Professional Education. The curriculum can be understood as a form of production, organization and registration of school knowledge, so it needs to be linked to a reflective practice and consider that cultural and social relations interact within it within the educational environment. There are also, within the school context, attitudes and values subliminally transmitted by social relations and daily routines, which do not appear implicit in the formal curriculum and contribute to the formation of the school being, this is called the hidden curriculum. The study was conducted within a qualitative approach and included a bibliographic research, descriptive and non-participant observation. It was possible to identify several elements that, although not explained in the official curriculum, are part of the school processes and spaces and contribute to the students' professional formation.